Experimental investigation on dynamic diffusion characteristics and mechanism of liquid kerosene jet in supersonic high-enthalpy inflow - Junlong Zhang; Naigang Cui; Guangjun Feng; Hongchao Qiu; Jiarui Zhang; Bohao Yan; Wen Bao (Fuel, 2026)

Multi-omics analysis reveals the molecular mechanism of silibinin rescue the toxic effects of butyl benzyl phthalate on porcine preimplantation embryos - Yu Li; Guangjun Huang; Na Li; Zihao Zhang; Hanwen Zhang; Qian Gao; Zhaokang Cui; Yi Jiang; Yilong Miao (Journal of Hazardous Materials, 2025)

Sodium dehydroacetate induces porcine oocyte toxicity by inhibiting TCA cycle activity and mitochondrial function, with nicotinamide mononucleotide as a potential protective agent - Na Li; Yu Li; Guangjun Huang; Hongyu Sun; Jiaqi Wu; Qian Gao; Zhaokang Cui; Yilong Miao (Food and Chemical Toxicology, 2025)

Marine Debris Detection in Real Time: A Lightweight UTNet Model - Junqi Cui; Shuyi Zhou; Guangjun Xu; Xiaodong Liu; Xiaoqian Gao (Journal of Marine Science and Engineering, 2025)
The increasingly severe issue of marine debris presents a critical threat to the sustainable development of marine ecosystems. Real-time detection is essential for timely intervention and cleanup. Furthermore, the density of marine debris exhibits significant depth-dependent variation, resulting in degraded detection accuracy. Based on 9625 publicly available underwater images spanning various depths, this study proposes UTNet, a lightweight neural model, to improve the effectiveness of real-time intelligent identification of marine debris through multidimensional optimization. Compared to Faster R-CNN, SSD, and YOLOv5/v8/v11/v12, the UTNet model demonstrates enhanced performance in random image detection, achieving maximum improvements of 3.5% in mAP50 and 9.3% in mAP50-95, while maintaining reduced parameter count and low computational complexity. The UTNet model is further evaluated on underwater videos for real-time debris recognition at varying depths to validate its capability. Results show that the UTNet model exhibits a consistently increasing trend in confidence levels across different depths as detection distance decreases, with peak values of 0.901 at the surface and 0.764 at deep-sea levels. In contrast, the other six models display greater performance fluctuations and fail to maintain detection stability, particularly at intermediate and deep depths, with evident false positives and missed detections. In summary, the lightweight UTNet model developed in this study achieves high detection accuracy and computational efficiency, enabling real-time, high-precision detection of marine debris at varying depths and ultimately benefiting mitigation and cleanup efforts.

Experimental and Theoretical Investigation of Initial Irreversible Critical Damage State of Red Mudstone - Guangjun Cui; Chang Xia; Cuiying Zhou; Zhen Liu; Lihai Zhang (Rock Mechanics and Rock Engineering, 2024)

Simulation of cyclic slow-to-fast landslides based on the coupled creep and frictional slip model - Chang Xia; Zhen Liu; Guangjun Cui; Cuiying Zhou (Computers and Geotechnics, 2024)

Experimental study on Diels-Alder addition of conjugated dienes directly from cracking C5 fraction by continuous micro-channel reactors - Zehao Jing; Tingting Ge; Hui Guo; Yuchao Li; Zhou Li; Cuncun Zuo; Ming Wang; Haofei Huang; Lin Guo; Guangjun Cui (Fuel, 2023)

A Coupled Tensor–DEM–FEM Model for the Whole Process of Internal Fine-Scale Damage to Surface Damage in Red-Bed Soft Rocks in the Coastal Area of South China - Chang Xia; Yongtao Wu; Guangjun Cui; Jin Liao; Zhen Liu; Cuiying Zhou (Journal of Marine Science and Engineering, 2023)
Calculation and characterization of the whole process of internal microscopic damage to surface damage in red-bed soft rock is a theoretical research difficulty and an urgent need for engineering safety protection. However, the current study cannot accurately and directly correlate internal and external damage. Therefore, in this paper, a coupled tensor–DEM–FEM model is proposed to deal with surface damage by indoor triaxial test digital image processing (DIC), internal damage by FJM acoustic emission study, and internal and external damage by moment tensor correlation. The study demonstrates that the whole process damage process of the red-bed soft rock peak front can be divided into six distinct phases, with early damage beginning with the elastic phase; the local strain divergence value begins to spiral out of control during the period of crack acceleration development; the overall acoustic emission intensity distribution is in the range of [−8.5, −6.3] in two dimensions and in the range of [−11, −9] in three dimensions; the R were between −40 and 40, which corresponded to the results of the indoor tests. A model has been developed that allows a direct reflection of the whole damage process. The method can be used to better understand the disaster mechanism and guide engineering practice.

Mars climate change research: Perspective of sulfur replacing carbon in martian sedimentary rocks - Cuiying Zhou; Guangjun Cui; Linghua Kong; Zhen Liu; Wei Huang; Lei Yu; Lihai Zhang (Icarus, 2023)

A Coupled Macroscopic and Mesoscopic Creep Model of Soft Marine Soil Using a Directional Probability Entropy Approach - Cuiying Zhou; Guangjun Cui; Wanyi Liang; Zhen Liu; Lihai Zhang (Journal of Marine Science and Engineering, 2021)
To mitigate the risk of structural failure in coastal engineering caused by soft marine soil creep, this study presents a coupled macroscopic and mesoscopic creep model of soft marine soil to predict long-term deformation behavior of the soil. First, the mesoscopic characteristics of soft marine soil (e.g., pore, particle, and morphological characteristics) under different external pressures were obtained using a scanning electron microscope. Then, both the mesoscopic and macroscopic characteristics of soil were quantified using directional probability entropy and then used as inputs to develop the model. The model predictions agree with the experimental data. In addition, the experimental results indicate linear negative correlations between porosity and pore ratio with stress—the relationships between the fractal dimension of pore distribution and probability entropy of particle orientation under stress are generally nonlinear. Further, results of sensitivity analysis indicate that the probability entropy of particle orientation is one of the most critical parameters governing long-term creep deformation behavior of soft marine soil.

Effects of Different Temperatures on the Softening of Red-Bed Sandstone in Turbulent Flow - Zhen Liu; Xinfu He; Guangjun Cui; Cuiying Zhou (Journal of Marine Science and Engineering, 2019)
The rates of chemical reactions are highly dependent on temperature, meaning that the actual geological rock mass is affected by different temperatures. Only when the temperature effect is considered can the mechanism of the influence of temperature on the interaction between water and rock be further understood. It was found that the condition of turbulent flow is more likely to promote the softening of red-bed sandstone than the conditions of laminar flow and static water in an experimental study on the softening effects of different flow patterns on red-bed sandstone. Therefore, based on a multi-functional self-circulating open channel hydraulic test system, this paper designs and completes equal volume saturated tests of red-bed sandstone at low temperature (1 °C), medium temperature (23 °C), and high temperature (45 °C) under the turbulent conditions of three equal temperature gradients. The chemical action of the circulating solution in water flow at different temperatures, the propagation of micro-cracks in rock and the changes in mechanical indexes are discussed. The influence laws and mechanisms of the different temperatures on the softening of red-bed sandstone in turbulent flow are revealed. The results show that low-temperature flow can inhibit the softening of red-bed sandstone in the range of 1–45 °C. With the increase in water flow temperature, the development degrees of micro-structures and the mechanical damage of the corresponding rock become more notable. That is, temperature affects the physical and chemical water-rock interactions and then changes the internal structure of rock, thus affecting the softening and failure processes of red-bed sandstone. The study provides a theoretical basis for the further investigation of the softening laws and mechanisms of other red layered soft rocks by temperature under turbulent conditions.

Role of PTP/PTK trans activated insulin-like signalling pathway in regulation of grasshopper (Oedaleus asiaticus) development - Babar Hussain Chang; Boyang Cui; Hidayat Ullah; Shuang Li; Kun Hao; Xiongbing Tu; Guangjun Wang; Xiangqun Nong; Mark Richard McNeill; Xunbing Huang; Zehua Zhang (Environmental Science and Pollution Research, 2019)

Screening of high toxic Metarhizium strain against Plutella xylostella and its marking with green fluorescent protein - Qianqian Cui; Yi Zhang; Yanchao Zang; Xiangqun Nong; Guangjun Wang; Zehua Zhang (World Journal of Microbiology and Biotechnology, 2014)